Genetic polymorphisms near IL-21 gene associated with Th17 cytokines confer risk for systemic lupus erythematosus in Chinese Han population. (March 2019) - Meng, Yanming; Xu, Heng; Zhang, Shouyue; Zhang, Junlong; Wang, Lu; Tang, Honghu; Wu, Yongkang
Objective: Interleukin-21 (IL-21) contributes to expansion, differentiation, and modulation of various immunocompetent cells. Deregulated production of IL-21 plays a role of cardinal significance in the pathogenesis of systemic lupus erythematosus (SLE). We aimed to determine whether single nucleotide polymorphisms (SNP) near the IL-21 gene have significant association with SLE susceptibility and the T helper-related inflammatory cytokine profile of SLE patients. Methods: We enrolled 460 SLE patients and 460 healthy controls. Whole genome analysis was used to investigate different genes including IL-21. Loci rs11725913, rs11937669, rs7676539, rs111438679, rs115935829, rs373549, rs4487356, and rs79923870 were further genotyped using an improved multiplex ligation detection reaction technique. Susceptibility, levels of Th-related inflammatory cytokines, and some clinical indexes of SLE patients were analyzed. Results: rs11725913 and rs11937669 were identified for association with SLE in Chinese Han Population. The allelic frequency of rs11725913 approached significance (odds ratio (OR) (95% Confidence Interval (CI)) = 1.431 (1.122–1.825), P  = 0.004). GT genotype at rs11725913 and GA genotype at rs11937669 were associated with SLE susceptibility (OR (95% CI) = 1.448 (1.074–1.952), P  = 0.015; OR (95%CI) = 1.356 (1.013–1.815), P  = 0.040, respectively). Dominant model analysis provided us with further validation (rs11725913: OR (95%CI) = 1.502 (1.126–2.004), P  = 0.006; rs11937669: OR (95%CI) = 1.356 (1.025–1.793), P  = 0.033). Cases with rs11937669 risk GA-genotype had higher serum IL-6 concentration than others ( P  = 0.022). Dominant model analysis showed that patients with the wild type (AA-genotype) at rs11937669 had significantly lower soluble CD40 ligand ( P  = 0.029) but higher IL-17A ( P  = 0.040) compared with others. Cases carrying rs11725913 T allele had higher gamma glutamyl transpeptidase level ( P  = 0.045) than those without. Conclusions: We identified two new loci, rs11725913 and rs11937669, associated with SLE risk in Chinese Han population. This research provided a new insight into the significant relationship between polymorphisms upstream IL-21 and Th17 inflammatory response, which suggest that the sequence upstream of the IL-21 gene is an important region involved in the Th17-related pathway.